2010
DOI: 10.5194/acp-10-7169-2010
|View full text |Cite
|
Sign up to set email alerts
|

Role of aldehyde chemistry and NO<sub>x</sub> concentrations in secondary organic aerosol formation

Abstract: Aldehydes are an important class of products from atmospheric oxidation of hydrocarbons. Isoprene (2-methyl-1,3-butadiene), the most abundantly emitted atmospheric non-methane hydrocarbon, produces a significant amount of secondary organic aerosol (SOA) via methacrolein (a C4-unsaturated aldehyde) under urban high-NOx conditions. Previously, we have identified peroxy methacryloyl nitrate (MPAN) as the important intermediate to isoprene and methacrolein SOA in this NOx regime. H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
174
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(201 citation statements)
references
References 63 publications
(89 reference statements)
18
174
4
Order By: Relevance
“…For product identification, all detected ions in this study were assumed to be deprotonated molecules. All ion formulae suggested for oligomer series 1A-4A in the present study agreed with those suggested in a recent study by Chan et al (2010). The products of series 1A, 2A, 3A, and 4A were identified as 2-methylglyceric acid oligoesters and their mononitrates, monoformates, and monoacetates, respectively.…”
Section: Identification Of Productssupporting
confidence: 79%
See 2 more Smart Citations
“…For product identification, all detected ions in this study were assumed to be deprotonated molecules. All ion formulae suggested for oligomer series 1A-4A in the present study agreed with those suggested in a recent study by Chan et al (2010). The products of series 1A, 2A, 3A, and 4A were identified as 2-methylglyceric acid oligoesters and their mononitrates, monoformates, and monoacetates, respectively.…”
Section: Identification Of Productssupporting
confidence: 79%
“…Similar oligomer signals were found at m/z 266, 368, 470, 572, 674, 776 (series 2A); m/z 249, 351, 453, 555, 657, 759 (series 3A); and m/z 263, 365, 467, 569, 671, 773 (series 4A). The mass numbers of these oligomer signals agreed with those measured in previous studies (Surratt et al, 2006;Chan et al, 2010). In this study, a new series of oligomer signals with a regular mass difference of 102 amu was observed at m/z 327, 429, 531, 633, and 735 (series 5A).…”
Section: Lc-tof Mass Spectrumsupporting
confidence: 78%
See 1 more Smart Citation
“…2). Chan et al, 13 in a series of photochemical chamber experiments, proposed that the main fate of A* is collisional stabilization (producing A) followed by reaction with molecular oxygen to form an alkylperoxyl radical (B), where the beta-peroxyl moiety attacks at the carbonyl carbon to form a di-oxoketone (DOK) and NO 2 as a co-product (Fig. 2, mechanism 2).…”
Section: Introductionmentioning
confidence: 99%
“…For example, earlier studies of the MPAN + OH system 20,21 did not measure SOA formation and were conducted with high mixing ratios of NO x (blind to the formation of nitrogen products). More-recent laboratory studies of Chan et al 13 and Lin et al 18 were performed with methacrolein, such that products from MPAN oxidation and from the OH addition route of methacrolein (B55% probability) were formed simultaneously, complicating the analysis. 8 The theoretical study of Kjaergaard et al 17 has yet to be experimentally validated.…”
Section: Introductionmentioning
confidence: 99%